The Organizational Development Strategy of a Waste Bank at Bank Sampah Regensi by Using SWOT Analysis - Lutfi Yulian; Pitri Yandri (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2022)
Waste is still one of the factors of environmental pollution. The rate of increase in waste every year increases without the addition of TPS. Along with the confirmation of the Corona virus and many community activities are done from home, such as shopping and online selling activities. Without realizing it, these activities cause new waste, such as tape, bubble wrap, and plastic wrap. Waste reduction and management can be done through waste banks. As in Cisoka Indah Regensi Housing, there is a Bank Sampah Regensi. The Bank Sampah Regensi is run by teenagers in RT.03 RW.06. Where their average age is still a student. This study aims to identify the weaknesses, strengths, opportunities and threats of the Bank Sampah Regensi and provide recommendations for the best strategies that the Bank Sampah Regensi can take for the development of the Bank Sampah Regensi organization. This research is a qualitative descriptive research with descriptive analysis techniques and quantitative SWOT of IFAS and EFAS. The sampling technique uses purposive sampling. The results of this study show that the Regence Waste Bank is in quadrant I, meaning that the organization is in a strong position and has the opportunity. The recommended strategy is to support aggressive policies (growth oriented strategy), namely: sensitivity training, team building, and management by objective. As well as the Strenghts-Opportunity strategy and the Weakness-Opportunity strategy.